The treatment of urban wastewaters by membrane methods - Seminska, O.O.; Kucheruk, D.D.; Balakina, M.M.; Goncharuk, V.V. (Reports of the National Academy of Sciences of Ukraine, 2016)
The efficiency of the preconditioning of Kyiv's wastewater for its further purifying by reverse osmosis plants with filtration through a sand filter with the 1—2 mm faction loading followed by the microfiltration on a ceramic microfilter with clay minerals is investigated. It is established that the combination of chosen water pretreatment methods contributes to the efficient stable operation of the reverse osmosis membrane, providing a reduction of the source water turbidity by 99.9 %, phosphate content in it by 98.8 %, and total organic carbon by 94.8...99.9 % at constant values of its specific productivity to the permeate selection ratio of 80 %.